THE EFFECT OF DIFFERENT ENERGY AND PROTEIN BALANCE TO THE POST WEANING BALI PIGS BODY DIMENSIONS - I P., Galang K.; Sumadi, I K.; Ariana, I N. T. (Jurnal Peternakan Tropika, 2018)
This study aim to determine the effect of different energy and protein balance of ration to the post weaning bali pigs body dimensions. The conducted at  Taman Wedasari, Banjar Batu Paras, Padangsambian Kaja Village, West Denpasar for  12 weeks. Completely randomized design (CRD) was used with four treatmens, and three replications. Those treatments were (A): ME/CP 175 (2800 kkal/16%), (B): ME/CP 164 (2950 kkal/ 18%), (C): ME/CP 155 ( 3100 kkal/20%), (D) : ME/CP 148 (3250 kkal/22%) respectively for level of energy and protein balance of ration fed animal. Variables of body dimensions observed were body lenght, chest abdominal circumference, shoulder, hip and back heght. The result showedthat all of the body dimensions observed were noy significantly difference, as the food comsumption was similar. Thence, their growth as showed by final weight wese also similar (P>0,05). It can be concluded that different balance of energy and protein given not resulted in different body dimensions of the post weaning Bali pigs   Keywords: Bali Pig, Body Dimension, Energy and Protein Balance.